Incidence and Trends in Immune Reconstitution Inflammatory Syndrome Associated With Histoplasma capsulatum Among People Living With Human Immunodeficiency Virus: A 20-Year Case Series and Literature Review. (28th March 2019) - Melzani, Alessia; de Reynal de Saint Michel, Regis; Ntab, Balthazar; Djossou, Felix; Epelboin, Loic; Nacher, Mathieu; Blanchet, Denis; Demar, Magalie; Couppie, Pierre; Adenis, Antoine
Abstract: Background: Histoplasmosis is among the main acquired immunodeficiency syndrome (AIDS)–defining conditions in endemic areas. Although histoplasmosis has a worldwide distribution, histoplasmosis-associated immune reconstitution inflammatory syndrome (IRIS) in people living with human immunodeficiency virus (PLHIV) is rarely reported. This study aimed to describe the incidence and features of histoplasmosis-associated IRIS in a cohort of PLHIV. Methods: A retrospective multicenter study was conducted in French Guiana from 1 January 1997 to 30 September 2017. The target population was represented by PLHIV who presented an episode of histoplasmosis within 6 months after antiretroviral therapy initiation. We used a consensual IRIS case definition, submitted to the agreement of 2 experts. Each case was described using a standardized questionnaire, and all patients gave informed consent. Results: Twenty-two cases of histoplasmosis-associated IRIS were included (14 infectious/unmasking and 8 paradoxical), with an overall incidence rate of 0.74 cases per 1000 HIV-infected person-years (95% confidence interval, 0.43–1.05). Mean age was 40.5 years. The ratio of males to females was 1:4. Median time to IRIS was 11 days (interquartile range 7–40 days) after antiretroviral therapy initiation. The main clinical presentation was fever, without any specific pattern, and disseminated disease. We reported 2 severe cases and partial or complete recovery at 1 month was the rule. Twenty-two cases were identified in the literature with similar characteristics. Conclusions: Histoplasmosis-associated IRIS incidence was low but generated significant morbidity in PLHIV. In endemic areas, screening for latent or subclinical histoplasmosis should be implemented before antiretroviral therapy initiation. Abstract : Histoplasmosis-associated immune reconstitution inflammatory syndrome (IRIS) in people living with human immunodeficiency virus (PLHIV) is rarely reported. We describe a low incidence of histoplasmosis-associated IRIS along with significant morbidity. A histoplasmosis screening strategy is required in PLHIV initiating antiretroviral therapy.